2020
DOI: 10.3389/fnins.2020.00862
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Functional and Structural Changes in the 5xFAD Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer's disease is characterized by the aberrant deposition of protein in the brain and is the leading cause of dementia worldwide. Increasingly, there have been reports of the presence of these protein hallmarks in the retina. In this study, we assayed the retina of 5xFAD mice, a transgenic model of amyloid deposition known to exhibit dementia-like symptoms with age. Using OCT, we found that the retinal nerve fiber layer was thinner in 5xFAD at 6, 12, and 17 months of age compared with wild-type littermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 61 publications
7
44
1
Order By: Relevance
“…Criscuolo et al 18 also reported reduced pERG amplitude in the same mice, suggesting RGC dysfunction. Likewise, Lim et al 22 showed small b-wave amplitude losses in the 5xFAD mice at 6 and 12 months of age that did not meet the threshold for statistical significance. For older 5xFAD mice (17 months) they reported that the b-wave amplitude elicited by a high luminance flash was significantly reduced, and reductions in the a-wave were also noted 22 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Criscuolo et al 18 also reported reduced pERG amplitude in the same mice, suggesting RGC dysfunction. Likewise, Lim et al 22 showed small b-wave amplitude losses in the 5xFAD mice at 6 and 12 months of age that did not meet the threshold for statistical significance. For older 5xFAD mice (17 months) they reported that the b-wave amplitude elicited by a high luminance flash was significantly reduced, and reductions in the a-wave were also noted 22 .…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, Lim et al 22 showed small b-wave amplitude losses in the 5xFAD mice at 6 and 12 months of age that did not meet the threshold for statistical significance. For older 5xFAD mice (17 months) they reported that the b-wave amplitude elicited by a high luminance flash was significantly reduced, and reductions in the a-wave were also noted 22 . Lim et al 22 found the scotopic threshold response to be reduced at all ages, which also suggested RGC dysfunction.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations